2019
DOI: 10.1515/icom-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

User-Centered Development of Smart Glasses Support for Skills Training in Nursing Education

Abstract: An ageing society creates an increasing need for a well-trained nursing staff. In particular, physically demanding motion sequences must be learned correctly to preserve carers’ long-term health. During training, support in practical skills training must also leave the carers’ hands free to allow them to perform the motion sequences unencumbered. Wearables might provide the necessary information “hands-free” and thus support skills training. In this paper, we present and discuss a User-Centered Design approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Previous studies showed that higher levels of attention and better learning engagement were achieved when implementing XR in education [ 22 - 24 ]. Using smart glasses enhances users’ engagement in performance [ 25 ]. Smart glasses improve the efficiency of practice, helping students master each skill with timely information without compromising performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that higher levels of attention and better learning engagement were achieved when implementing XR in education [ 22 - 24 ]. Using smart glasses enhances users’ engagement in performance [ 25 ]. Smart glasses improve the efficiency of practice, helping students master each skill with timely information without compromising performance.…”
Section: Introductionmentioning
confidence: 99%
“…Google Glass launched in 2013 and demonstrated a viable use of OST HMDs through various situated applications in information visualization and augmented reality using images and instructions. Since then, commercial smartglasses from Microsoft [13][14][15][16][17][18][19][20][21], Google [22,23], HTC [7,8], Vuzix [24], Epson [25,26] and Brother [27] have integrated a wearable display with a computationally sufficient computing unit that provides connectivity and a multi-modal user interface. For example, the latest OST HMDs such as HoloLens 2 and MagicLeap One provide high-resolution displays (i.e., up to 2048 × 1080), a wide FoV (i.e., 52 and 50 degrees), and tracking and control capabilities.…”
Section: Wearable Displaysmentioning
confidence: 99%
“…Kim et al [33] No No Nursing Education Klinker et al [13] No No Medical Kopetz et al [22] No No Nursing Education Rochlen et al [25] No No Medical Huang et al [27] No No Medical Aebersold et al [34] No No Medical Hanna et al [14] Yes Yes Medical Yoon et al [23] Yes Yes Medical Lacy et al [35] Yes Yes Medical Rio et al [26] Yes Yes Medical Greenberg et al [32] Yes Yes Medical Liu et al [15] Yes Yes Medical Meijer et al [36] Yes Yes Medical Andersen et al [37,38] Yes Yes Medical STAR [16][17][18][19] Yes Yes Medical Mitsuno et al [20] Yes Yes Medical Mentis et al [39] Yes Yes Medical, Industrial Lin et al [40] Yes Yes Medical Gasques et al [21] Yes Yes Medical Hassan et al [41] Yes Yes Medical Giuseppe et al [42] Yes Yes Industrial Semsar et al [31] Yes Yes Medical Wang et al [7] Yes Yes Industrial Wang et al [8] Yes Yes Physical Task…”
Section: Remoteness Mentoring Domainmentioning
confidence: 99%
“…Previous studies showed that higher levels of attention and better learning engagement were achieved when implementing XR in education [22][23][24]. Using smart glasses enhances users' engagement in performance [25]. Smart glasses improve the efficiency of practice, helping students master each skill with timely information without compromising performance.…”
Section: Introductionmentioning
confidence: 98%